Composite nanofiltration membrane as well as preparation method and application thereof
Preparation of EDA-TPA-CONs/HPAN composite membrane through interface polymerization, solving the problems of mechanical stability and pollution sensitivity of composite nanofiltration membranes in dye wastewater treatment, achieving efficient dye retention and anti-pollution ability, ensuring dye Efficiency and stability of wastewater treatment.
Patent Information
- Application Number
- CN202411617822.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-10
AI Technical Summary
The existing composite nanofiltration membranes have poor mechanical stability and sensitivity to natural organic pollution when treating dye wastewater, resulting in increased filtration resistance and reduced efficiency, limiting their application in dye wastewater treatment.
Interfacial polymerization of terephthaldehyde and ethylenediamine was carried out on the surface of HPAN film to form an EDA-TPA-CONs/HPAN composite film. By adjusting the reaction conditions and monomer concentration, the degree of cross-linking and stability of the film are improved. , increase the tightness of the pore size to improve the interception rate.
Achieve high retention rate and anti-pollution ability of dyes, especially significant retention properties for positive and negative electrical dyes and binary dyes, and maintain stable performance under long-term operation and mechanical stirring conditions, with high flux recovery rate and reduced flux Low rate.
Smart Images

Figure CN119281140A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite membranes, and in particular relates to a composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] In the dye industry, about 80% of synthetic dyes are used to dye textiles, resulting in a large amount of dye wastewater. Considering the strong toxicity of synthetic dyes, it is very important for the environment and human health to use effective methods to treat dye wastewater and ensure that it meets safe emission standards. Existing common dye wastewater treatment methods include flocculation sedimentation, adsorption, biodegradation and membrane separation technology. Among them, membrane separation technology has attracted widespread attention due to its advantages such as high efficiency, low energy consumption, green environmental protection and simple equipment. The material and preparation method of the membrane are the core of membrane manufacturing, which largely determines the comprehensive performance of the membrane.
[0003] Among many materials, two-dimensional covalent organic networks (2D CONs) have attracted extensive attention due to their adjustable pore size, stable physical and chemical properties, and robustness. At present, there are many common methods for preparing CONs membranes, including solvothermal method, layer-by-layer stacking, hybrid assembly and other methods. However, the above methods all have problems such as harsh reaction conditions, long reaction time, loose membrane structure, poor mechanical properties, and membrane surface defects, which limit the application of CONs membranes. Among the many preparation methods, interfacial polymerization (IP) has the characteristics of mild reaction conditions, self-limiting reaction, and unlimited reaction area. It can react at solid / liquid, gas / liquid, and liquid / liquid interfaces at room temperature. IP has solved the problem of the difficulty in preparing large-area continuous ultra-thin, defect-free two-dimensional self-supporting CONs membranes to a certain extent. However, due to the poor mechanical stability of self-supporting CONs membranes, it is often necessary to obtain tough CONs membranes through tedious multiple reactions. Therefore, researchers introduced microporous support membranes to synthesize CONs composite membranes to improve the mechanical stability of the membranes. However, in the process of preparing CONs composite membranes by most IPs, it is often necessary to sacrifice reaction time to obtain CONs composite membranes with high crystallinity.
[0004] At present, CONs composite membranes have been widely used in water treatment, but membrane fouling has limited their further development and application. Among the various organic pollutants that affect membrane fouling, natural organic matter (NOM) is the most important one. Pollutants including humic acid, polysaccharides and proteins. NOM is widely present in various water bodies and has complex material characteristics. It can not only combine with other substances to form precursors of harmful compounds, which endangers human health, but also aggravates the pollution of composite membranes, resulting in extremely high filtration resistance and significantly reducing filtration efficiency, thereby increasing the difficulty of wastewater treatment.
[0005] Therefore, providing a CONs composite membrane with strong anti-pollution ability, good stability and capable of being used for water treatment is a technical problem that researchers in this field need to solve urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a composite nanofiltration membrane and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a composite nanofiltration membrane comprises the following steps:
[0009] Terephthalaldehyde and ethylenediamine are dissolved in mesitylene and deionized water respectively, and interfacial polymerization reaction is carried out on the surface of HPAN membrane at the junction of the two phases to form a continuous ultra-thin CONs nanofiltration membrane in situ, thereby obtaining the composite nanofiltration membrane.
[0010] Beneficial effects: IP has the characteristics of mild reaction conditions, self-limited reaction, and unlimited reaction area. It can react at solid / liquid, gas / liquid, and liquid / liquid interfaces at room temperature. IP has solved the problem of difficulty in preparing large-area continuous ultra-thin, defect-free CONs composite membranes to a certain extent.
[0011] Preferably, the aldehyde monomer is terephthalaldehyde; and the aliphatic diamine monomer is ethylenediamine.
[0012] Beneficial effects: The more nucleophilic aliphatic flexible diamine monomer accelerates the Schiff base reaction and the formation of CONs, shortening the reaction time.
[0013] Preferably, the concentrations of the aldehyde monomer and the aliphatic diamine monomer are both 12.5-20 mmol / L.
[0014] Beneficial effects: The increase in monomer concentration increases the cross-linking degree of CONs, reduces the pore size of the composite membrane, and ensures a high retention rate for dyes.
[0015] Preferably, the interfacial polymerization reaction is specifically as follows: placing the organic solution of the aldehyde monomer on one side of the HPAN membrane, placing the aqueous solution of the aliphatic diamine monomer on the other side of the HPAN membrane, and the amine monomer in the aqueous phase and the aldehyde monomer in the organic phase undergo a Schiff base reaction on the surface of the HPAN membrane at the interface between the two phases.
[0016] Beneficial effect: The interlocking interface region between the separation layer and the support layer of the CONs composite membrane makes the combination of the two more firm, thus ensuring the stability of the composite membrane.
[0017] Preferably, the polymerization reaction is first reacted at room temperature for 2-6 hours, and then placed under 60° C. for drying and heat treatment for 10 minutes.
[0018] Beneficial effects: The reaction conditions at room temperature are mild and energy-free; the reaction time of 2-6 hours is faster than the traditional IP reaction of 72 hours; the heat treatment at 60°C for 10 minutes can thermally fix the separation layer and the support layer, thereby enhancing the stability of the composite membrane.
[0019] Preferably, the HPAN is prepared by a non-solvent phase conversion method, which specifically comprises the following steps:
[0020] The casting liquid is placed on a non-woven fabric with a pore size of 200 μm, and the film is cast by scraping. After forming, it is immediately placed in deionized water. After two rounds of phase conversion, the obtained polyacrylonitrile membrane is taken out from the deionized water, placed in an alkaline aqueous solution for heating and hydrolysis, and then rinsed with deionized water until neutral to obtain HPAN.
[0021] Beneficial effects: The hydrolysis process of polyacrylonitrile fiber involves the conversion of its surface cyano groups (-CN) into carboxyl groups (-COOH), which enhances the hydrophilicity and other properties of polyacrylonitrile.
[0022] Preferably, the casting solution is a mixture of polyacrylonitrile, polyvinyl pyrrolidone and N,N-dimethylformamide;
[0023] The mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is (10-25wt%): (3-18wt%).
[0024] Preferably, the heating hydrolysis condition is heating hydrolysis at 50° C. for 1 hour.
[0025] Beneficial effect: The above heating conditions are conducive to accelerating the hydrolysis reaction.
[0026] A composite nanofiltration membrane is prepared by a method for preparing a composite nanofiltration membrane.
[0027] Beneficial effects: The preparation process provided by the present invention has low energy consumption, is simple and fast, and has mild conditions.
[0028] The invention discloses an application of a composite nanofiltration membrane in sewage treatment.
[0029] Beneficial effects: The composite nanofiltration membrane of the present invention has a retention performance of >90% of common dyes and high anti-fouling performance when applied in sewage treatment.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] The present invention provides a composite nanofiltration membrane and a preparation method and application thereof, which can simply, quickly and gently prepare a nanofiltration composite membrane with extremely high stability and strong antifouling ability, and the composite nanofiltration membrane can be used for dye wastewater treatment. The EDA-TPA-CONs / HPAN composite membrane obtained by the present invention has significant interception performance for both positive and negative dyes, and the interception rates are RB≥97%, MG≥94%, CV≥98%, MB≥99%, and AF=92±1% respectively. It shows excellent selectivity in the separation of binary dyes and mixed drugs. In addition, the EDA-TPA-CONs / HPAN composite membrane shows excellent stability. The interception rate and flux of bengalensis remain basically unchanged within 340 minutes of long-term continuous operation and after 5 cycles of testing, the interception rate of bengalensis is still above 90% after continuous ultrasound at 16kHZ for 180 minutes and mechanical stirring at 100rpm for 24 hours. The EDA-TPA CONs composite membrane has excellent anti-BSA pollution ability. After dynamic anti-BSA cycle, the flux recovery rate (FRR) of the composite membrane is 96%, while the flux decline rate (FDR) is only 6%. The above results show that the composite nanofiltration membrane obtained by the present invention has great value potential in sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Some of the drawings provided in this application are intended to provide a further understanding of the present application. The illustrative embodiments of the present application and their descriptions are intended to explain the present application and do not constitute improper limitations on the present application.
[0033] In the attached picture:
[0034] Figure 1 This is the preparation process of EDA-TPA-CONs / HPAN composite membrane.
[0035] Figure 2 (a) is the ATR-FTIR spectra of HPAN and EDA-TPA-CONs / HPAN composite film; (b) is the XRD spectrum of independent EDA-TPA CONs; (c) is the XRD spectrum of EDA-TPA-CONs / HPAN composite film and HPAN film; (d) is the water contact angle of the composite film at different reaction times; (e) is the water contact angle of HPAN and the optimal EDA-TPACONs / HPAN composite film; (f) is the zeta potential of HPAN and EDA-TPACONs / HPAN composite film; (g) is the thermogravimetric analysis result of EDA-TPA CONs / HPAN composite film; (h) is the pore size analysis result of BET test of EDA-TPA-CONs / HPAN composite film; (i) is the structure of EDA and TPA monomers and the schematic diagram of CONs synthesis;
[0036] Figure 3To characterize the morphology of EDA-TPA-CONs / HPAN composite membrane;
[0037] Among them, (a) is the SEM image of the HPAN film surface; (b)-(f) are the SEM images of the EDA-TPA-CONs / HPAN composite film surface at different reaction times; (g)-(h) are the cross-sectional SEM images of the EDA-TPA-CONs / HPAN composite film at 3h and 6h; (i) is the 3D AFM image of the EDA-TPA-CONs / HPAN composite film;
[0038] Figure 4 is the separation performance of EDA-TPA composite membrane;
[0039] Among them, (a) is a schematic diagram of the cross-flow filtration system for nanofiltration experiments; (b) is an optimization diagram for different reaction times; (c) is an optimization diagram for different monomer concentrations; (d)-(e) are the nanofiltration test results of positive and negative dyes; (f) is the nanofiltration test result of small drug molecules; (g) is the UV-visible absorption spectrum before and after the separation of mixed dyes; (h) is a diagram of the selective separation mechanism of mixed binary systems; (i) is the UV-visible absorption spectrum before and after the separation of mixed drugs;
[0040] Figure 5 (a) is a long-term stability test; (b) is a cyclic stability test; (c) is a stability test under different ultrasonic times; (d) is the ultraviolet absorption spectrum of the composite membrane before and after separation of tiger red after ultrasound; (e) is a mechanical stirring stability test; (f) is a physical picture of the composite membrane before and after mechanical stirring for 24 hours; (g) is a radar chart of the comprehensive stability of the EDA-TPA-CONs / HPAN composite membrane; (h) is a digital picture of the interfacial polymerization film-forming reaction without a support layer;
[0041] Figure 6 It is the result of anti-pollution test;
[0042] Among them, (a) is the anti-pollution mechanism diagram of HPAN and EDA-TPA-CONs / HPAN composite membrane; (b) is the dynamic anti-BSA test of EDA-TPA-CONs / HPAN composite membrane; (c) is the results of various anti-pollution indicators of EDA-TPA-CONs / HPAN composite membrane; (d) is the dynamic anti-BSA test of HPAN membrane; (e) is the results of various anti-pollution indicators of HPAN membrane; (f) is the static anti-pollution fluorescence inverted microscope micrograph of BSA of HPAN membrane; (g) is the static anti-pollution fluorescence inverted microscope micrograph of BSA of EDA-TPA-CONs / HPAN composite membrane;
[0043] Figure 7 To test and compare the nanofiltration performance of different working dyes;
[0044] Figure 8 These are the UV absorption spectra of different dye small molecules before and after separation. DETAILED DESCRIPTION
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0047] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0048] Among them, sodium hydroxide (NaOH, AR) was obtained from Tianjin Fuyu Fine Chemical Co., Ltd.;
[0049] Dimethylformamide (AR, 99.5%) was purchased from Tianjin Tianli Chemical Reagent Co., Ltd.;
[0050] Bengal red (99%) and vincristine (HPLC ≥ 98%) were purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0051] Terephthalaldehyde (98%), mesitylene (AR, 97%), methyl green (85%), berberine hydrochloride (HPLC ≥ 98%), and chlorogenic acid (HPLC ≥ 98%) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0052] Anhydrous ethylenediamine (AR, 97%) was purchased from Damao Chemical Reagent Co., Ltd.;
[0053] Congo red (99%), methyl orange (99%), sodium fluorescein (99%), methylene blue (99%), acid fuchsin (99%), polyacrylonitrile PAN (MW 85000), polyvinyl pyrrolidone (MW 58000), and bovine serum albumin (BSA, 99%) were purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0054] Fluorescein isothiocyanate-bovine serum albumin (FITC-BSA, 95%) was purchased from Beijing Solebow Technology Co., Ltd.
[0055] The room temperature or normal temperature described in the embodiments of the present invention refers to 25±3°C.
[0056] Example 1
[0057] A method for preparing a composite nanofiltration membrane comprises the following steps:
[0058] (1) Preparation of HPAN membrane by non-solvent phase inversion method: Add magnetic rotor, polyacrylonitrile and polyvinyl pyrrolidone into a glass bottle, the mass ratio of polyacrylonitrile and polyvinyl pyrrolidone is (10-25wt%): (3-18wt%), then add N,N-dimethylformamide to dissolve, and then stir with a magnetic stirrer until the mixture is transparent yellow, defoam at room temperature, and obtain a casting solution. The defoamed casting solution is placed on a non-woven fabric with a pore size of 200μm, and cast into a membrane by scraping. After forming, it is immediately placed in deionized water. After two rounds of phase inversion, the polyacrylonitrile membrane is taken out of the deionized water, placed in a NaOH solution (concentration of 2mol / L), heated and hydrolyzed in a water bath at 50℃ for 1 hour, and then rinsed with deionized water to neutrality to obtain HPAN, which is stored in deionized water for later use.
[0059] (2) Preparation of EDA-TPA-CONs / HPAN composite membrane Figure 1 As shown: the HPAN membrane obtained in step (1) is placed between the upper and lower layers of the diffusion cell, 40 ml of deionized water and 40 ml of mesitylene are measured and placed in two wide-mouth bottles, then terephthalaldehyde (12.5 mmol / L) is weighed and dissolved in the mesitylene organic phase to obtain a terephthalaldehyde solution, and then ethylenediamine (12.5 mmol / L) is measured and dissolved in the water phase to obtain an ethylenediamine solution. Then the terephthalaldehyde solution is injected into the upper layer of the diffusion cell using a syringe, and the ethylenediamine solution is injected into the lower layer of the diffusion cell using a syringe. The reaction diffusion cell is placed at room temperature, and the solution is diffused to allow the terephthalaldehyde monomer and the ethylenediamine monomer to polymerize on the HPAN membrane for 3 hours, and then the composite membrane is taken out and placed in a 60°C oven for reaction for 10 minutes. After the reaction is completed, it is repeatedly rinsed with ethanol and ultrapure water to remove the residual reaction monomers to terminate the reaction, and a composite nanofiltration membrane is obtained, which is recorded as EDA-TPA-CONs / HPAN composite membrane.
[0060] Example 2
[0061] A method for preparing a composite nanofiltration membrane, which is different from Example 1 only in that the concentration of the terephthalaldehyde solution in step (2) is 7.5 mmol / L, and the concentration of the ethylenediamine solution is 7.5 mmol / L. The other process steps and parameters are the same as those in Example 1.
[0062] Example 3
[0063] A method for preparing a composite nanofiltration membrane, which is different from Example 1 only in that the concentration of the terephthalaldehyde solution in step (2) is 10 mmol / L, and the concentration of the ethylenediamine solution is 10 mmol / L. The other process steps and parameters are the same as those in Example 1.
[0064] Example 4
[0065] A method for preparing a composite nanofiltration membrane, which is different from Example 1 only in that the concentration of the terephthalaldehyde solution in step (2) is 15 mmol / L, and the concentration of the ethylenediamine solution is 15 mmol / L. The other process steps and parameters are the same as those in Example 1.
[0066] Example 5
[0067] A method for preparing a composite nanofiltration membrane, which is different from Example 1 only in that the concentration of the terephthalaldehyde solution in step (2) is 17.5 mmol / L, and the concentration of the ethylenediamine solution is 17.5 mmol / L. The other process steps and parameters are the same as those in Example 1.
[0068] Example 6
[0069] A method for preparing a composite nanofiltration membrane, which is different from Example 1 only in that the concentration of the terephthalaldehyde solution in step (2) is 20 mmol / L, and the concentration of the ethylenediamine solution is 20 mmol / L. The other process steps and parameters are the same as those in Example 1.
[0070] Example 7
[0071] A method for preparing a composite nanofiltration membrane, which differs from Example 1 only in that in step (2), the reaction diffusion cell is placed at room temperature for 2 hours, and then the composite membrane is taken out and placed in a 60° C. oven for drying for 10 minutes. The other process steps and parameters are the same as those in Example 1.
[0072] Example 8
[0073] A method for preparing a composite nanofiltration membrane, which differs from Example 1 only in that in step (2), the reaction diffusion cell is placed at room temperature for 4 hours, and then the composite membrane is taken out and placed in a 60° C. oven for drying for 10 minutes. The other process steps and parameters are the same as those in Example 1.
[0074] Example 9
[0075] A method for preparing a composite nanofiltration membrane, which differs from Example 1 only in that in step (2), the reaction diffusion cell is placed at room temperature for 6 hours, and then the composite membrane is taken out and placed in a 60° C. oven for drying for 10 minutes. The other process steps and parameters are the same as those in Example 1.
[0076] Technical effect:
[0077] 1. Performance Characterization
[0078] The morphology of the EDA-TPA-CONs / HPAN composite films was observed by field emission scanning electron microscopy (SEM, EM-30plus) and atomic force microscopy (AFM, DimensionIcon), and all samples were sprayed with a thin layer of Au / Pd to enhance their conductivity.
[0079] Fourier transform infrared (FTIR) spectra were collected on an IS10 spectrometer in the wavenumber range of 1000–4000 cm -1 .
[0080] The film was tested using the attenuated total reflectance (ATR) mode.
[0081] X-ray diffraction (XRD) patterns were performed on an XRD-6100 at room temperature with a scanning range of 2–60° and a scanning rate of 0.01°·s -1 (voltage = 40 kV, current = 40 mA).
[0082] The water contact angles were measured by DSA100S at room temperature.
[0083] The thermogravimetric curve of the membrane was measured using NETZSCH STA449F3 to characterize the thermal stability of the membrane.
[0084] The pore size distribution was determined by measuring the N2 adsorption-desorption isotherms at 77 K in a liquid nitrogen bath.
[0085] The zeta potential of the membrane was measured using the streaming potentiometry method on an electrokinetic analyzer from Anton Paar GmbH.
[0086] The characterization results are as follows:
[0087] The chemical composition of the CONs composite membrane was investigated by ATR-FTIR spectroscopy. Figure 2 As can be seen in part (a), at 1640cm -1 The characteristic C=N stretching band appeared at , confirming the formation of the imine framework structure.
[0088] The results of X-ray diffraction (XRD) measurements by independent EDA-TPA CONs are shown in Figure 2 As shown in part (b), it can be seen that the crystallinity of independent CONs is average, which may be caused by the flexible fatty amines in the CONs unit building blocks.
[0089] Then, X-ray diffraction (XRD) measurements were also performed on the EDA-TPA-CONs / HPAN composite film and the HPAN independent substrate. Figure 2As shown in part (c), it can be seen that the three diffraction peaks in the EDA-TPA-CONs / HPAN composite film basically coincide with the diffraction peaks of the original HPAN substrate film, but there is no obvious independent diffraction peak in EDA-TPA CONs, which may be due to the masking of the HPAN diffraction peak.
[0090] The hydrophilicity of the membrane is shown in Figure 2 As shown in part (d), it can be seen that the hydrophilicity of the membrane gradually increases with the increase of reaction time. Such changes can be attributed to the hydrophilic groups in the unreacted monomers on the surface, such as the aldehyde group in terephthalaldehyde and the amino group in ethylenediamine. As the reaction time increases, the hydrophilic groups on the membrane surface continue to increase, so the hydrophilicity of the membrane becomes more hydrophilic as time goes by. Figure 2 Part (e) shows the water contact angle between HPAN and the optimal composite film.
[0091] Zeta potential test results are as follows Figure 2 As shown in part (f), it can be seen that under the condition of pH = 7, the surface of the composite membrane has a negative charge of -30 mV.
[0092] Simultaneous thermal analysis (TGA) of EDA-TPA-CONs / HPAN composite films Figure 2 As shown in part (g), it can be seen that after 345 °C, there is an obvious weight loss, which is caused by the decomposition of CONs, indicating that the composite membrane has good thermal stability.
[0093] The microporous properties of the composite membrane are as follows Figure 2 As shown in (h), it can be seen that the average pore size of the membrane is 9.817 angstroms.
[0094] The structures of the reaction monomers ethylenediamine and terephthalaldehyde and the CONs structures are as follows: Figure 2 As shown in part (i).
[0095] In order to observe the internal structure of EDA-TPA-CONs / HPAN composite membrane more clearly, Figure 3 (a)-(h) show the SEM surface and cross-sectional images of the composite membrane and HPAN substrate membrane at different reaction times. Figure 3 Part (a) Figure 3 As can be seen in part (b), compared with the HPAN substrate, a ridge-like structure is observed on the surface of the EDA-TPA-CONs / HPAN composite film, further proving the success of the Schiff base reaction to synthesize the selective layer. Figure 2 The characterization results are consistent. Figure 3As shown in parts (c)-(f), the formation and evolution process of the composite film can be observed. The composite films at different reaction times show similar morphology as a whole. As the reaction time increases, the density of CONs deposited on the surface of the composite film increases. Figure 3 Parts (g) and (h) are SEM cross-sectional images of the composite membranes prepared after 3h / 6h of reaction. It can be seen intuitively that the composite membranes are composed of a finger-like structure support layer at the bottom and a dense selective layer at the top. As the reaction time increases, the thickness of the membrane gradually thickens with the accumulation of CONs. The thickness of the membrane gradually increases from 253.62nm at 3h to about 365.31nm at 6h. Figure 3 Part (i) is the AFM 3D image of the composite membrane. From the AFM 3D image, we found that the membrane surface is relatively smooth, with Ra of only about 25.5nm, which lays the foundation for the anti-BSA ability and enhances the anti-fouling ability.
[0096] 2. Performance evaluation of EDA-TPA-CONs / HPAN composite membrane
[0097] The interception performance of the EDA-TPA-CONs / HPAN composite membrane and the HPAN membrane obtained in Example 1 was tested using a small test machine (TYLG-17) produced by Shandong Bona Biotechnology Group Co., Ltd., and the flux and dye interception rate of the membrane were recorded. The device consists of the following six components: a water pump, a membrane unit, a regulator, a pressure gauge, an electrical instrument, and a pipeline frame. The effective filtration area of the test machine is 2.54 cm 2 Before formally recording the data, pre-pressurize with deionized water at a test pressure of 2 bar to ensure a stable flux before formal testing. Then record the flux every 15 minutes, and each experiment is repeated at least three times.
[0098] Pure water flux (J w ,Lh -1 m -2 bar -1 ) is defined as shown in formula (1):
[0099] J W =V / P×A×Δt (1)
[0100] Wherein, P (bar) is the test pressure;
[0101] V(L) is the permeate volume;
[0102] A(m 2 ) is the effective filtration area;
[0103] t(h) is the collection time.
[0104] The retention rate of the membrane was determined using dyes red bengal (RB, -), acid fuchsin (AF, -), methyl orange (MO, -), methyl green (MG, +), crystal violet (CV, +), and methylene blue (MB, +). Binary mixed dye separation was tested in water. Each dye solution contained 5 mg / L of RB and 5 mg / L of MB. The dye concentration was measured using a UV-visible spectrophotometer (TU-1901) to calculate the dye retention rate (R, %), and the calculation method was shown in formula (2):
[0105] R=(1-C P / C f )×100% (2)
[0106] Among them C f and C P are the concentrations of feed and permeate solutions, respectively.
[0107] The separation performance results of EDA-TPA-CONs / HPAN composite membrane are as follows:
[0108] like Figure 4 As shown in part (a), the separation performance of the EDA-TPA-CONs / HPAN composite membrane was tested using a cross-flow device.
[0109] Firstly, the effect of different reaction times on the nanofiltration performance of composite membranes was investigated. Figure 4 As shown in part (b), as the reaction time increases from 2 h to 3 h, the rejection rate of the EDA-TPA-CONs / HPAN composite membrane increases from 75.3% to 92%, and the flux is 20.5 L·m -2 ·h -1 bar -1 As the reaction time continued to increase, the retention rate of the membrane remained relatively stable, but the flux gradually decreased to 7.2 L·m -2 ·h -1 bar -1 The reason for the above changes may be that as the reaction time of the EDA-TPA-CONs / HPAN composite membrane increases, the membrane thickness continues to increase, and the mass transfer resistance gradually increases, resulting in a decrease in flux. Therefore, the membrane thickness can be adjusted by simply adjusting the reaction time, and then the flux can be adjusted. Considering the rejection rate and flux comprehensively, 3h reaction time was selected as the optimal reaction time condition for subsequent research.
[0110] The effect of the concentration of the reactive monomer on the nanofiltration performance of the composite membrane was further investigated. Figure 4Part (c). As the monomer concentration increased from 7.5 mmol / L to 10 mmol / L, the rejection rate increased rapidly from 36% to 63%. When the concentration increased to 12.5 mmol / L, the membrane showed a significant rejection rate of 97.3% and a flux of 28.9 L·m -2 ·h -1 bar -1 , the monomer concentration continued to increase, the retention rate remained relatively stable, but the flux continued to decrease to 18.18 L·m -2 ·h -1 bar -1 The above phenomenon is attributed to the fact that the increase in monomer concentration increases the cross-linking degree of CONs and reduces the pore size. Therefore, based on the trade-off between retention rate and flux, 12.5 mmol / L was used as the optimal monomer concentration for nanofiltration performance testing and characterization.
[0111] Common cationic dyes and anionic dyes were selected as dye model pollutants to study the nanofiltration performance of EDA-TPA-CONs / HPAN composite membrane for water-soluble pollutants. Nanofiltration tests were performed after pre-pressure at 2 bar. The test results are shown in Figure 2. Figure 4 As shown in parts (d) and (e), the composite membrane has significant interception performance for both positive and negative charged dyes, and the interception rates for macromolecular dyes are RB ≥ 97% and MG ≥ 94%, respectively. The interception rates for small molecular dyes are AF: 92 ± 1%, MO ≥ 66%, CV ≥ 98%, and MB ≥ 99%, respectively. The results are intuitively reflected and verified by UV-visible spectra ( Figure 8 ). In this process, it was found that the positively charged dyes always maintained an ultra-high retention rate, while the retention rate of negatively charged dyes decreased as the molecular weight decreased. The above phenomenon can be attributed to size screening and electrostatic interaction. When the diameter of the dye molecule is larger than the pore size, size screening plays a dominant role in the separation process. When the diameter of the dye molecule is smaller than the pore size, it cannot be intercepted by size screening. At this time, electrostatic interaction also plays an important role in the membrane separation process. Combined with zeta potential analysis ( Figure 2 In part (f), there is a significant electrostatic attraction between the negatively charged and oppositely charged molecules on the surface of the EDA-TPA-CONs / HPAN composite membrane. The positively charged dye is retained on the membrane surface under the electrostatic interaction, while the negatively charged dye passes through the membrane pores along with the water molecules.
[0112] In addition, common drug molecules were separated, and the results are as follows Figure 4As shown in part (f), it can be seen that the retention rates of the EDA-TPA-CONs / HPAN composite membrane for these four representative drug molecules are: berberine hydrochloride (MW: 336.36, +), 80%, chlorogenic acid (MW: 354.31, 0), 91.5%, sodium fluorescein (MW: 356.3%, -), 48.5%, vincristine (MW: 824.96, 0), 55.7%. In connection with the molecular diameter and charge analysis of these drug molecules, the difference in retention rates of different drug molecules is mainly caused by the molecular charge. Since berberine hydrochloride ionizes with a positive charge in an aqueous solution system, while sodium fluorescein ionizes with a negative charge, and vincristine does not ionize, berberine hydrochloride has an excellent retention rate relative to sodium fluorescein and vincristine under electrostatic interaction. The significant retention rate of chlorogenic acid may be due to the adsorption of chlorogenic acid on the membrane surface.
[0113] In order to verify the selective separation ability of EDA-TPA-CONs / HPAN composite membrane for binary mixed systems, we conducted selective separation experiments using mixed dyes and drugs with different charges. Figure 4 As shown in parts (g)-(h), the binary mixed dye of methyl orange and methylene blue appears green in water. After separation, the positively charged methylene blue small molecules are retained on the membrane due to electrostatic interaction, while the negatively charged small molecules of methyl orange can smoothly pass through the composite membrane and enter the permeate together with water molecules, and the permeate after final separation appears orange. This precise separation result can also be verified by UV-visible spectroscopy, and similar results have been obtained for the binary mixed system of medicinal small molecules ( Figure 4 (i)). The positively charged berberine hydrochloride is retained on the composite membrane due to electrostatic interaction, while the negatively charged sodium fluorescein passes through the composite membrane into the retentate. This result is also verified by UV-visible spectroscopy. In summary, the synergistic effect of size screening and electrostatic interaction plays an important role in the nanofiltration process of the composite membrane.
[0114] 3. Stability test
[0115] First, the long-term stability of the EDA-TPA-CONs / HPAN composite membrane and HPAN membrane obtained in Example 1 was tested at an operating pressure of 1 bar. Secondly, the pre-pressure operation was carried out at 2 bar for 45 minutes, and then soaked in ethanol for 10 minutes and rinsed, and the RB flux and retention rate of each cycle were recorded to test the cyclic stability. Further, after continuous ultrasound at 16kHZ for 30, 60, 120, and 180 minutes, the retention performance of RB was tested to evaluate the ultrasonic stability. Then, it was stirred in a shaker at an oscillation rate of 100rpm for 24 hours, and the retention rate of the composite membrane after stirring for bengalensis in water was tested to evaluate the stability against mechanical stirring.
[0116] Membrane stability is a key parameter of the membrane. The long-term test stability results of the composite membrane are as follows: Figure 5 As shown in part (a), it can be seen that the composite membrane showed a continuous strong and stable dye removal ability for red bengal in water during the long-term test within 340 minutes, the retention rate was constant at more than 90%, and the flux remained basically constant during this period. Secondly, we also tested the recyclability of the membrane, testing it at 2 bar for 30 minutes, and then immersing it in an ethanol solution for 10 minutes. Because the red bengal dye can be quickly dissolved in ethanol, the red bengal can be washed away by immersion in ethanol. In the first 5 cycles, the ultra-high retention rate of more than 90% for RB in water was continuously maintained, and the flux and the initial flux of the membrane remained at a relatively stable level ( Figure 5 (b)). This indicates that the dye retained on the surface of the composite membrane during the nanofiltration process can be restored to its initial performance by simply immersing and rinsing the composite membrane. Then, the composite membrane's ultrasonic resistance was tested under 16 kHz ultrasound for different times. The results showed that within 180 minutes of ultrasound, the composite membrane still maintained an ultra-high retention rate of more than 90% for bengalensis in water ( Figure 5 (c) of the Figure 5 Part (d) shows the composite membrane after ultrasound and the UV absorption spectrum before and after separation of bengalensis. In addition, the membrane's ability to resist mechanical agitation was also tested. The results showed that after mechanical agitation for 24 hours at a shaker speed of 100 rpm, the polymer layer on the membrane surface did not fall off significantly ( Figure 5 In (f) part), we also tested the composite membrane after stirring with bengalensis in water, and still maintained a stable retention performance of more than 95% ( Figure 5 The above tests on the stability of the composite membrane show that the composite membrane has excellent stability, which means that the composite membrane obtained by the present invention has durability and stability under various adverse conditions. Figure 5 Part (g) is a radar chart of the comprehensive stability of the composite membrane, indicating that the composite membrane has ultra-high stability. Figure 5 The middle part (h) shows the two-phase interface polymerization without a substrate. An obvious film layer is formed at the junction of the two phases. When it is squeezed with a straw, there is no obvious damage on the surface of the film, indicating that it has a certain toughness.
[0117] 4. Dynamic anti-fouling performance test
[0118] It is well known that membranes usually have serious scaling problems in practical water treatment applications, which usually leads to a decrease in flux and thus reduces the efficiency of membrane separation. In fact, hydrophilicity, surface roughness and membrane surface charge characteristics are usually factors that affect the antifouling performance of composite membranes. To this end, we comprehensively evaluated the antifouling performance of composite membranes using two methods: BSA dynamic and static antifouling.
[0119] The EDA-TPA-CONs / HPAN composite membrane and HPAN membrane obtained in Example 1 were subjected to dynamic antifouling test evaluation using BSA as the standard pollutant, and were pre-pressed with deionized water for 30 minutes before the start of the experiment. The dynamic antifouling experiment was divided into two cycles. In the first cycle, the membrane was pre-pressed with pure water at 2 bar for 60 minutes, and the pure water flux (J) was recorded every 10 minutes. Wt ), then 1 g / L BSA solution was used instead of pure water for 90 min under the same conditions, and the BSA permeation flux (J) was recorded every 15 min. P ), and then the membrane was immersed in deionized water for 45 minutes and rinsed repeatedly to ensure that the contaminants on the membrane surface were completely removed, completing the first cycle. In the second cycle, the operation in the first cycle was repeated, that is, pure water was used for membrane filtration for 60 minutes, and the pure water flux (J) was recorded every 10 minutes. W1 ), 1 g / L BSA solution was used for testing, and the BSA permeation flux (J) was recorded every 15 min. P1 ). Flux recovery rate (FRR), flux decline rate (FDR), complete fouling rate (R t )Reversible scaling rate (R r ) and irreversible fouling rate (R ir ) is calculated as shown in equations (3)-(7):
[0120] FRR=J W1 / J Wt ×100% (3)
[0121] FDR=(J W1 -J Wt ) / J w1 ×100% (4)
[0122] R t =(J w1 -J P / J w1 )×100% (5)
[0123] R r =(J W1 -J P ) / J w ×100% (6)
[0124] R ir =(J W1 -J w ) / J w ×100% (7)
[0125] The results of the BSA dynamic anti-pollution experiment are as follows Figure 6As shown, in the BSA dynamic anti-fouling experiment, the anti-fouling performance of EDA-TPA-CONs / HPAN composite membrane and HPAN is expressed by two indicators: flux decline rate FDR (%) and flux recovery rate FRR (%). The anti-fouling performance of HPAN membrane and EDA-TPA-CONs / HPAN composite membrane was tested by using 1g / LBSA as a protein pollution source. Two cyclic filtration processes were carried out, including three pure water filtration processes: 0-60, 150-210 and 300-360 minutes and two BSA filtration processes: 60-150 and 210-300 minutes. After two cycles of repeated rinsing, the BSA anti-fouling performance of the membrane was analyzed. The results are shown in Figure 6 Part (b) and Figure 6 As shown in part (c), the water flux of the EDA-TPA-CONs / HPAN composite membrane after the first cycle is 18 L·m -2 ·h -1 bar -1 , FRR is 96%, and FRR of HPAN membrane is 17%. After the second cycle, the water flux and FRR of EDA-TPA-CONs / HPAN composite membrane decreased slightly, but still maintained excellent anti-fouling performance. However, HPAN membrane could not recover to the initial flux ( Figure 6 (d) and (e) in the figure). By comparing the flux decrease rates of the two, the flux decrease rate of the composite membrane is only 6%, while the flux decrease rate of HPAN is as high as 83%. This shows that the addition of the polymer layer on the EDA-TPA-CONs / HPAN composite membrane is the reason for the improved anti-fouling ability of the composite membrane. Compared with the zeta potential of the HPAN membrane, the surface of the composite membrane has a stronger negative charge, which enhances the charge repulsion on the membrane surface. The probability of negatively charged BSA protein depositing on the membrane under the action of electrostatic repulsion is reduced, which can effectively prevent the direct contact between the surface of the EDA-TPA-CONs / HPAN composite membrane and pollutants. In conjunction with the AFM results, the relatively smooth membrane surface also increases the possibility of BSA on the membrane surface being washed away. In addition, due to the dense deposition of CONs on the HPAN surface, the pore size of the composite membrane is reduced, making it difficult for BSA to enter the pores ( Figure 6 (a) The finger-like pores of HPAN are larger, making it easier for BSA to enter the pores and cause blockage. In summary, the electrostatic repulsion on the membrane surface and the smooth and dense membrane surface play an important role in the anti-fouling ability of the composite membrane.
[0126] 5. Static anti-pollution BSA experiment
[0127] By designing FITC-BSA as a model protein, the static anti-fouling ability of proteins on the surface of the composite membrane was qualitatively revealed, the fluorescence intensity on the surface of the EDA-TPA-CONs / HPAN composite membrane and the HPAN basement membrane was recorded by a fluorescence inverted microscope, the adsorption of FITC-BSA on the EDA-TPA-CONs / HPAN composite membrane and the HPAN membrane was observed, and the anti-fouling ability of the two was compared. The specific steps are as follows:
[0128] First, the EDA-TPA-CONs / HPAN composite membrane obtained in Example 1 was cut into an area of 0.5 cm×0.5 cm and soaked in a neutral PBS solution (10 mL) for 24 hours. The membrane was then taken out and immersed in a 5 mL PBS solution containing 0.1 mg / mL FITC-BSA, and gently shaken at room temperature for 4 hours under dark conditions. Then, the membrane was taken out and rinsed three times with PBS to remove any potential unadsorbed FITC-BSA. Finally, the membrane was observed using a fluorescent inverted microscope. For comparison, a static anti-fouling comparative test of the HPAN membrane (obtained in step (1) of Example 1) was also performed, and the membrane treatment method was the same as above.
[0129] According to the results, Figure 6 The green fluorescence in the middle (f) part covers the entire HPAN basement membrane, indicating that a large amount of FITC-BSA is adsorbed on the HPAN surface. The strong green fluorescence intensity indicates that the HPAN basement has almost no anti-fouling ability, which is consistent with the results of dynamic anti-BSA. The green fluorescence on the surface of the EDA-TPA-CONs / HPAN composite membrane is only scattered on the surface of the composite membrane ( Figure 6 (g), indicating that the composite membrane surface has a strong resistance to protein adhesion. Combined with the results of dynamic BSA, it shows that the composite membrane loaded with CONs on the HPAN membrane surface has a strong anti-fouling ability.
[0130] Figure 7 To test and compare the nanofiltration performance of different working dyes;
[0131] Figure 7 The sources of work for comparison are:
[0132] [1] F.Sheng,
[0133] [2]N.Basel,Q.Liu,L.Fan,Q.Wang,N.Xu,Y.Wan,Q.Dong,Z.Huang,T.Guo,Surfacecharge enhanced synthesis ofTpEB-based covalent organic framework(COF)membrane for dye separation with three typical charge properties,Sep.Purif.Technol.303(2022)122243.
[0134] [3]K.Banjerdteerakul,H.Peng,K.Li,Ceramic hollow fibre supportedcovalent organic framework membranes prepared by direct interfacialpolymerisation-potential for efficient dye removal from wastewater,J.Membr.Sci.683(2023)121852.
[0135] [4]Y.Zhang,H.Ye,D.Chen,N.Li,Q.Xu,H.Li,J.He,J.Lu,In situ assembly ofacovalent organic framework composite membrane for dye separation,J.Membr.Sci.628(2021)119216.
[0136] [5]P.-P.Li,Z.-L.Xu,Y.-X.Fang,D.Pandaya,L.-L.Gao,R.Ding,Novel TFCmembrane with crosslinked PMIA active layer fabricated by the T-FLO techniquefor dye desalination,J.Membr.Sci.681(2023)121779.
[0137] [6]Y.Liu,J.Du,H.Wu,C.Cong,H.Zhang,J.Wang,Z.Wang,Antifoulingstreptomycin-based nanofiltration membrane with high permselectivity for dye / salt separation,Sep.Purif.Technol.297(2022)121443.
[0138] [7]Y.Wu,M.Gao,W.Chen,Z.Lü,S.Yu,M.Liu,C.Gao,Efficient removal ofanionic dye by constructing thin-film composite membrane with high perm-selectivity and improved anti-dye-deposition property,Desalination 476(2020)114228.
[0139] [8]Y.Chen,C.He,High salt permeation nanofiltration membranes based onNMG-assisted polydopamine coating for dye / salt fractionation,Desalination 413(2017)29-39.
[0140] [9]T.Zhang,P.Li,S.Ding,X.Wang,High permeability compositenanofiltration membrane assisted by introducing TpPa covalent organicframeworks interlayer with nanorods for desalination and NaCl / dye separation,Sep.Purif.Technol.270(2021)118802.
[0141]
[10] Y.Yang,W.Ma,G.Li,C.Zhong,X.Yan,W.Huang,S.Zhang,Z.Cai,Z.Lin,Polyamide-Supported Covalent Organic Framework Nanomembranes for MolecularSize-Dependent Selective Separation,ACS Appl.Nano Mater.4(12)(2021)13967-13975.
[0142]
[11] In-situ grown covalent organic framework nanosheets on graphenefor membrane-based dye / salt separation,J.Membr.Sci.581(2019)321-330.
[0143]
[12] M.Q.Seah,W.J.Lau,P.S.Goh,A.F.Ismail,Greener synthesis offunctionalized-GO incorporated TFN NF membrane for potential recovery ofsaline water from salt / dye mixed solution,Desalination 523(2022)115403.
[0144]
[13] H.Yuan,K.Li,D.Shi,H.Yang,X.Yu,W.Fan,P.J.S.Buenconsejo,D.Zhao,Large-Area Fabrication ofUltrathin Metal-Organic Framework Membranes,Adv.Mater.35(18)(2022)12.
[0145]
[14] X.Gong,G.Zhang,H.Dong,H.Wang,J.Nie,G.Ma,Self-assembledhierarchical heterogeneous MXene / COF membranes for efficient dye separations,J.Membr.Sci.657(2022)120667.
[0146] Depend on Figure 7 It can be seen that compared with other existing research results, the performance of the EDA-TPA-CONs / HPAN composite membrane provided by the present invention has significant advantages. Figure 8 Shown are the UV absorption spectra of different dyes before and after separation by the EDA-TPA-CONs / HPAN composite membrane. It can be seen that the composite membrane has a good retention effect on different dye molecules.
[0147] In summary, the EDA-TPA-CONs / HPAN composite membrane provided by the present invention can be used for dye wastewater treatment, and has significant interception performance for both positive and negative dyes, wherein RB≥97%, MG≥94%, CV≥98%, MB≥99%, and AF is approximately 92±1%, and at the same time, it exhibits excellent selectivity for the separation of binary dyes and mixed drugs. In addition, the EDA-TPA-CONs / HPAN composite membrane exhibits excellent stability. Within 340 minutes of long-term continuous operation and after 5 cycles of testing, the interception rate and flux of red tiger in water remain basically unchanged. After continuous ultrasound at 16kHZ for 180 minutes and mechanical stirring at 100rpm for 24 hours, the interception rate of red tiger in water is still above 90%. In addition, the EDA-TPA-CONs / HPAN composite membrane has excellent anti-BSA scaling ability. After dynamic anti-BSA circulation, the flux recovery rate (FRR) of the composite membrane is 96%, while the flux decline rate (FDR) is only 6%.
[0148] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a composite nanofiltration membrane, characterized in that: The following steps are involved: Terephthalaldehyde and ethylenediamine are dissolved in mesitylene and deionized water respectively, and interfacial polymerization reaction is carried out on the surface of HPAN membrane at the junction of the two phases to form a continuous ultra-thin CONs nanofiltration membrane in situ, thereby obtaining the composite nanofiltration membrane.
2. The method for preparing a composite nanofiltration membrane according to claim 1, characterized in that: The aldehyde monomer is terephthalaldehyde; and the aliphatic diamine monomer is ethylenediamine.
3. The method for preparing a composite nanofiltration membrane according to claim 1, characterized in that: The concentrations of the aldehyde monomer and the aliphatic diamine monomer are both 12.5-20 mmol / L.
4. The method for preparing a composite nanofiltration membrane according to claim 1, characterized in that: The interfacial polymerization reaction is specifically as follows: placing the organic solution of the aldehyde monomer on one side of the HPAN membrane, placing the aqueous solution of the aliphatic diamine monomer on the other side of the HPAN membrane, and the amine monomer in the aqueous phase and the aldehyde monomer in the organic phase undergo a Schiff base reaction on the surface of the HPAN membrane at the interface between the two phases.
5. The method for preparing a composite nanofiltration membrane according to claim 1, characterized in that: The polymerization reaction is firstly carried out at room temperature for 2 to 6 hours, and then heat-treated and dried at 60° C. for 10 minutes.
6. The method for preparing a composite nanofiltration membrane according to claim 1, characterized in that: The HPAN membrane is prepared by a non-solvent phase conversion method, which specifically includes the following steps: The casting liquid is placed on a non-woven fabric with a pore size of 200 μm, and the film is cast by scraping. After forming, it is immediately placed in water. After two rounds of phase conversion, the obtained polyacrylonitrile membrane is taken out from the deionized water, placed in an alkaline aqueous solution for heating and hydrolysis, and then rinsed with deionized water until neutral to obtain HPAN.
7. The method for preparing a composite nanofiltration membrane according to claim 6, characterized in that: The casting solution is a mixture of polyacrylonitrile, polyvinyl pyrrolidone and N,N-dimethylformamide; The mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is (10-25wt%): (3-18wt%).
8. The method for preparing a composite nanofiltration membrane according to claim 6, characterized in that: The heating hydrolysis condition is heating hydrolysis at 50° C. for 1 hour.
9. A composite nanofiltration membrane prepared by the method for preparing a composite nanofiltration membrane as described in any one of claims 1 to 8.
10. Use of the composite nanofiltration membrane as claimed in claim 9 in sewage treatment.